(untitled) (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2022)
The study was formulated to analyse social exclusion and extent of drugs addiction among youth in rural areas of Dir Lower, Khyber Pakhtunkhwa, Pakistan. A sample of 266 was randomly selected for data collection through interview. Statistical tools were used to measure the association between dependent and independent variables. The results show significant associations between drugs’ addiction led to severe form of social exclusion, social exclusion limited the access of drugs addict to basic facilities, deprived drugs user from employment and extent of drug’s addiction. Similarly, significant associations were depicted between social exclusion prevents the participation of drugs addict in religious/cultural events; restricted the social relationship with family and extent of drug’s addiction. Moreover, significant associations were accorded between socially excluded youth shows a greater level of social stigma, social exclusion leads to formation of risky behaviour, drugs addiction changes the life pattern of youth which evoked to social exclusion and extent of drug’s addiction. Thus, the government should make strategies for youth pertaining to preventions of drugs addiction with implementation at all institutional were put forward as the recommendation in the light of the current study.